Gestión y desarrollo Turístico en la Comunidad San Francisco de Cunuguachay, Parroquia Santiago de Calpi, Provincia de Chimborazo - Rojas Calero, Magaly Elizabeth (2019)
The present investigation was carried out to determine the management influence in the San Francisco de Cunuguachay community tourism development, in Santiago de Calpi parish, in Chimborazo province. In this investigation considered the tourist activity reality. The descriptive, field and correlational methods were used in quantitative and experimental researching design terms. Some statistical methods were used, such as Cronbach's Alpha, which allowed verifying the reliability of the instruments used, the software called SPSS, version 25, which allowed the analysis and interpretation of the results. Finally, the chi-square statistical used in the hypothesis testing tool, as a result of this investigation determined the destination planning, the identification of tourism products and services promotion and the tourism development influence in the communication significantly in San Francisco de Cunuguachay community. In response to the results of this researching work a management and planning tool called the Community Tourism Management Model was proposed, which defines the actions that will contribute to the tourism development of the area.